REAKSI ADAT KURANGNYA PERLENGKAPAN UPACARA PERKAWINAN PADA MASYARAKAT DAYAK KANAYAN DI DESA TELUK BAKUNG KECAMATAN SUNGAI AMBAWANG KABUPATEN KUBU RAYA - NIM. A1011151151, SYARIFAH MELINDA (Jurnal Fatwa Hukum, 2023)
Abstrac In practice, in the Dayak Kanayatn Tribe community in Teluk Village. In practice in the Kanayatn Dayak Tribe community in Teluk Bakung Village, Sungai Ambawang District, Kubu Raya Regency, there are also people who only carry out marriages using traditional methods and when carrying out traditional marriage ceremonies they ask for certain equipment. must be complete for the traditional marriage ceremony according to the applicable customs, and if they do not have incomplete wedding equipment, then the traditional leader cancels the traditional marriage ceremony. The equipment for the traditional marriage ceremony must be complete. For example, equipment brought by men to give to women are rings, women's clothing items such as jomuh (sarong) and bojuh (shirt), decorative equipment (powder, lipstick and comb), toiletries (soap, shampoo, toothpaste, toothbrush) and palm wine (a drink made from glutinous rice).Based on the background, the problem in this research can be formulated as "What is the Traditional Reaction to the Incompleteness of Traditional Ceremonial Equipment for Marriage in the Dayak Kanayatn Community in Teluk Bakung Village, Sungai Ambawang District, Kubu Raya Regency?". Furthermore, based on the problem formulation, the aim of this research is to look for data and information, procedures, conditions, causal factors, legal consequences and legal remedies in implementing marriage according to customary law in the Dayak Kanayatn tribe community in Teluk Bakung Village, Sungai Ambawang District, Kubu Raya Regency. . This type of research uses empirical legal research methods.Based on the conclusions, it can be concluded that marriages according to customary law in the Dayak Kanayan community in Teluk Bakung village, Sungai Ambawang subdistrict, Kubu Raya district, carry out traditional ceremonies because of the advanced thoughts of the younger generation so that the implementation of traditional ceremonies can be simpler without reducing the meaning of the traditional ceremony itself. ; The factors causing the shift in the implementation of traditional marriages among the Dayak Kanayan community in Teluk Bakung village are economic factors, religious factors and the influx of other cultures; The legal consequences of the Tayakanayan marriage in Teluk Bakung village are that couples who have not completed the equipment required for the traditional ceremony are given the traditional sanction of "ngompank"; and The traditional reaction to the lack of equipment for the Dayak Kanayan wedding ceremony in Teluk Bakung village is that the traditional leader and traditional community are subject to legal sanctions to complete the equipment needed for the traditional ceremony if the marriage is not cancelled.Keywords: Traditional ceremonies, marriage, Dayak traditions  Abstrak           Pada prakteknya di masyarakat Suku Dayak Kanayatn di Desa Teluk Pada prakteknya di masyarakat Suku Dayak Kanayatn di Desa Teluk Bakung Kecamatan Sungai Ambawang Kabupaten Kubu Raya, ada pula masyarakat yang hanya melakukan perkawinan dengan  cara  adat istiadat  saja dan dalam melaksanakan upacara adat perkawinan yang meminta perlengkapan yang harus lengkap untuk upacara adat perkawinan sesuai adat istiadat yang berlaku, dan jika tidak mempunyai perlengkapan perkawinan secara tidak lengkap, maka pemuka adat membatalkan upacara adat perkawinan perlengkapan untuk upacara perkawinan adat terpenuhi lengkap semua. Seperti perlengkapan yang dibawa oleh pihak laki-laki untuk diberikan kepada  pihak  perempuan adalah cincin, perlengkapan  baju wanita seperti  jomuh  (sarung)  dan  bojuh  (baju), perlengkapan hias (bedak, lipstick dan sisir), perlengkapan mandi (sabun,sampo,odol,sikat gigi)  dan  tuak (minuman yang terbuat dari beras pulut).Berdasarkan latar belakang,, maka dapat dirumuskan masalah dalam penelitian ini  bahwa “Apa Reaksi Adat Tidak Lengkapnya Perlengkapan Upacara Adat Dalam Perkawinan Pada Masyarakat Dayak Kanayatn Di Desa Teluk Bakung Kecamatan Sungai Ambawang Kabupaten Kubu Raya ?”. Selanjutnya berdasarkan rumusaan masalah, maka tujuan penelitian ini adalah untuk mencari data dan informasi, tata cara, syarat, faktor penyebab, akibat hukum dan upaya hukum dalam pelaksanaan perkawinan menurut  hukum adat pada masyarakat Suku Dayak Kanayatn di Desa Teluk Bakung Kecamatan Sungai Ambawang Kabupaten Kubu Raya. Jenis Penelitian menggunakan metode  penelitian hukum empiris.     Berdasarkan kesimpulan maka dapat di simpulkan bahwa perkawinan menurut hukum adat pada masyarakat Dayak kanayan di desa teluk Bakung kecamatan sungai Ambawang kabupaten kubu Raya dilaksanakannya upacara adat karena majunya pemikiran-pemikiran generasi muda sehingga pelaksanaan upacara adat bisa lebih sederhana tanpa mengurangi makna dari upacara adat itu sendiri; Faktor penyebab terjadinya pergeseran pada pelaksanaan perkawinan adat pada masyarakat Dayak kanayan di desa teluk Bakung adalah dikarenakan faktor ekonomi, faktor agama dan faktor masuknya budaya lain; Akibat hukum perkawinan tayakanayan di desa teluk bakung bagi pasangan yang belum melengkapi perlengkapan yang dibutuhkan dalam upacara adat diberikan sanksi adat "ngompank"; dan Reaksi adat kurangnya perlengkapan dalam upacara perkawinan Dayak kanayan di desa teluk Bakung yaitu dikenakan sanksi hukum oleh ketua adat dan masyarakat adat untuk melengkapi perlengkapan yang dibutuhkan dalam upacara adat jika tidak dibatalkan perkawinannya.Kata Kunci : Upacara Adat, Perkawinan, Adat Dayak